ASSESSMENT KLASTER PERIKANAN (Studi Pengembangan Klaster Rumput Laut Kabupaten Sumenep) - ARMEN ZULHAM (SOCA: Jurnal Sosial Ekonomi Pertanian, 2007)
Cluster is the strategy for regional development to support local economic potency. Theopinion of fisheries cluster will be developed closed to that strategy, with the aim to establishof fisheries industrial complex. In the fisheries cluster complex, the industrial units encourageto foster the harmonize link among others to increase the economic growth. Researchconcerning seaweed cluster was conducted in Sumenep (Madura) in May 2007. The locationwas choice as the target area for the establishment the fisheries cluster complex. The purposesof this research were: i). to identify and study the fisheries industrial cluster complexcharacteristics related to the development of fisheries industry. ii). To study the characteristicand pattern linkages among industrial units in fisheries center related to institutionaldevelopment. iii). to generate suggested recommendation for seaweed cluster industrialcomplex in Sumenep district. Data were collected through survey in the respected area; therespondents covered the local government officers, seaweed farmers, seaweed processors,local traders, exporters, local transportation services and local leaders. The research findingsare: there are many seaweed industry units in Sumenep which can be use as the maincomponent to organize for the establishment the seaweed industrial cluster complex, thereexist the horizontal conflict among traders and seaweed processors to have the seaweed fromthe farmers. On the other hand the vertical relationship among industrial unit tends to makeasymmetric information on price and product criteria between traders and seaweed farmers.This research recommended the seaweed cluster industrial complex in Sumenep developbased on: consumer oriented, collective and cumulative approach. And the development ofSumenep’s seaweed cluster need three step, namely: preparation step, consolidation step andindependency / transfer step. There are two types of industries which can be as a core of theseaweed clusters in Sumenep, there are the seaweed chip industry or the seaweed chip andpowder industry.